Critical Limits of Sulfur in Relation to the Growth and Development of French-bean and Cauliflower in Acidic Soils of Northwestern Himalayas. Issue 19 (28th October 2021) - , Gourav; Sankhyan, Narender Kumar; Kumar, Pardeep; Sharma, Gurbhan D.; Sharma, Neelam
ABSTRACT: Sulfur deficiency is recognized as a constraint to crop production all over the world from last decade. The soils of Northwestern Himalayas are also administering sulfur deficiency. To achieve higher yields with better nutritive quality, the plant fertilization management must include sulfur. Critical-level approach hardly advocated in vegetables, and no reports of critical limits of S were reported in Northwestern Himalayas. The present experiment on French bean and cauliflower on 10 types of soil (varying in pH and clay content) was laid out in completely randomized design under glass house with five levels of sulfur (0, 10, 20, 30, and 40 kg ha −1 ). Application of sulfur significantly increased the yield of French-bean and cauliflower as compared to no application of sulfur. The highest yield was obtained with application of 40 kg S ha −1 in both the crops. The green pod yield of French-bean at 30 kg S ha −1 was statistically at par with 40 kg S ha −1 . Critical limits of sulfur in soil were 9.5 mg kg −1 and 10.5 mg kg −1 for French-bean and cauliflower, respectively. Critical limits of S in French-bean and cauliflower plants were 0.103 and 0.336% sulfur, respectively. Critical limits of S in French-bean and cauliflower will help to supply nutrients in balanced amount and to achieve sustainability in production.